100 esztendő öröksége - Béres, Zsuzsa (Gerundium, 2016)
The Heritage of 100 Years. The library of the University of Debrecen celebrated its centenary in 2016. The current selection offers a summary of the most significant ideas in the lectures presented at the memorial session on September 30, 2016. It also offers a survey of the relevant events of the University of Debrecen pertaining to the festive occasion.